Psychological Health Issues of Medical Staff During the COVID-19 Outbreak - Xie, Jun; Liu, Qi; Jiang, Xiaobing; Manandhar, Upasana; Zhu, Zhen; Li, Yuanyuan; Zhang, Bo (Frontiers in Psychiatry, 2021)
Abstract Background: The outbreak of novel coronavirus disease 2019 (COVID-19) has caused public panic and psychological health problems, especially in medical staff. We aimed to investigate the psychological effect of the COVID-19 outbreak on medical staff. Methods: A cross-sectional study was conducted to examine the psychological impact of medical staff working in COVID-19 designated hospitals from February to March 2020 in China. We assessed psychological health problems using the Symptom Check List 90 (SCL-90). Results: Among 656 medical staff, 244 were frontline medical staff and 412 general medical staff. The prevalence of psychological health problems was 19.7%. The SCL-90 scores in frontline medical staff were significantly higher than that in general medical staff (mean: 141.22 vs. 129.54, P < 0.05). Furthermore, gender (odds ratio (OR) = 1.53, 95% CI = [1.02, 2.30], P = 0.042 for female vs. male) and the burden of current work (OR = 7.55, 95% CI = [3.75, 15.21], P < 0.001 for high burden; OR = 2.76, 95% CI = [1.80, 4.24], P < 0.001 for moderate burden vs. low burden) were associated with increased risk of poor psychological status. Conclusions: Medical staff experienced a high risk of psychological health problems during the outbreak of COVID-19, especially for frontline medical staff. Psychological health services are expected to arrange for medical staff in future unexpected infectious disease outbreaks.